Traditional African Religion and Modern Christianity in Zaire: The Case of the Bira - Warkentin, Raija (Anthropologica, 2022)
The rural Bira of northeastern Zaire have been exposed to the Christian message for well over half a century. It was during the Belgian colonial period that the first Catholic and Protestant missionaries came to this region of Zaire. Today most Zairians belong to either the Catholic or Protestant church, and the Bira themselves are predominantly Catholic. The suppression of ancestor worship is the only area where mission Christianity has scored a triumph over the traditional religious life of the Bira. In contrast, witchcraft beliefs persist. As for the belief in God, it appears that the Bira have utilized Christianity to make their traditional God Mbali less remote and more caring, a change which has also made the Christian God more compassionate and forgiving of sins. Thus, Mbali-God is a creative response on the part of the Bira to the syncretic religious encounter.